Isolasi Dan Identifikasi Bakteri Kitinolitik Pada Air Payau Menggunakan Media Kitin Dari Tulang Sotong - Apriyanto; Aprilianti Idris, Sri; Rasak, Adriatman; Syahrani Ado, Marni (Yayasan Rahmatan Fiddunya Wal Akhirah, 2023)
Chitinolytic bacteria are a group of bacteria capable of producing chitinase enzymes. Chitinase enzyme is an enzyme that has the ability to degrade chitin. Chitinolytic bacteria can be isolated from soil and water. Brackish water is a breeding ground for chitinolytic bacteria because brackish water is a habitat for several types of chitin-producing animals such as shrimp, crabs and cuttlefish. This study aims to isolate and identify chitinolytic bacteria in brackish water. The type of research used is a descriptive experiment with the sampling technique carried out by one shot case study. From the observation of the identification of the morphology of bacteria on NA media and the results of the gram staining that has been carried out, the first sample was found to be bacteria with macroscopic characteristics of white, rhizopoid, smooth surface, flat elevation and gram-positive bacilli were found in gram staining. The second sample has morphological characteristics of white, round, smooth surface, convex elevation on gram staining found in the form of vibrio with gram negative.